How to formulate research questions and design studies for telehealth assessment and evaluation. (October 2017) - Fatehi, Farhad; Smith, Anthony C; Maeder, Anthony; Wade, Victoria; Gray, Leonard C
Planning a research strategy and formulating the right research questions at various stages of developing a telehealth intervention are essential for producing scientific evidence. The aim of research at each stage should correspond to the maturity of the intervention and will require a variety of study designs. Although there are several published evaluation frameworks for telemedicine or telehealth as a subset of broader eHealth domain, there is currently no simple model to guide research planning. In this paper we propose a five-stage model as a framework for planning a comprehensive telehealth research program for a new intervention or service system. The stages are: (1) Concept development, (2) Service design, (3) Pre-implementation, (4) Implementation, (5) Post-implementation, and at each stage a number of studies are considered. Robust evaluation is important for the widespread acceptance and implementation of telehealth. We hope this framework enables researchers, service administrators and clinicians to conceptualise, undertake and appraise telehealth research from the point of view of being able to assess how applicable and valid the research is for their particular circumstances.